Anchor Analysis of the FPSO Spread Mooring System During Offloading - Arif Fadillah; Natasyah Dewanti; Rizky Irvana (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
FPSO (Floating Production Storage and Offloading) is a moving floating structure to accommodate petroleum exploration results with a frequently used mooring system, namely spread mooring. To make it easier for the FPSO ship to not be able to rotate or even move when loading and unloading due to environmental influences, a spread mooring mooring system is needed with analysis of the mooring stress and anchor lifting force that occurs on the FPSO ship. To determine the anchor lifting power and tension on the mooring, the RAO formula is needed using the Jonswap method, which will give RAO results in response to environmental influences. In this case, the Jonswap method is used to determine matters related to the RAO response to environmental factors by analyzing the FPSO ship model from Maxsurf software, then continuing the analysis using Ansys software. From the RAO response we get the mooring tension and anchor lifting power to the influence of environmental forces. The results of the mooring spread analysis obtained the highest stress value of 6.141 x 105 N, with an anchor lifting force of 4.717 x 103 N.